Proposal of Industry 4.0 Maturity Model in the Energy Sector - Nebati, Emine Elif; Avunduk, Zehra Binnur; Akcan, Abdullah Fatih; Nebati, Emine Elif (Springer, 2024)
With the widespread use of the Internet, traditional methods that have been going on for a long time have begun to change. A new transformation has been entered with digital technologies. This transformation has brought about changes and developments in various sectors. The Industry 4.0 revolution has also provided the opportunity for significant transformations in the energy sector. In this study, research has been conducted on the changes digital transformation has created in the energy sector, how it affects the industry, and how it contributes. Within the scope of this research, a digital roadmap was created for a leading company in Türkiye’s energy sector, which tends to digitalize and focuses on development and innovation. Thus, a tool will be designed for the self-evaluation of institutions in the energy sector. In the model proposed within the scope of the study, a total of 25 criteria, including five main and twenty sub-criteria, were determined. It is aimed to measure the level of digital maturity for a company selected as an alternative with the determined criteria. In the study, the DEMATEL method was preferred in determining the criteria priorities in the first step of the application. The company’s digital maturity score was calculated in the second step and the results were shared. It is anticipated that the study will contribute to both the literature and the energy sector since the subject of digital transformation has been attracting attention and demand recently, and the methodology applied in this area is limited.
Keywords: DEMATEL; Digital Maturity Model; Energy Industry; Industry 4.0; Technology